Bureaucratic reform in the Ottoman Empire : the Sublime Porte, 1789-1922 - Findley, Carter V., 1941- (Princeton University Press, 1980)
From the author's preface: Sublime Porte--there must be few terms more redolent, even today, of the fascination that the Islamic Middle East has long exercised over Western imaginations. Yet there must also be few Western minds that now know what this term refers to, or why it has any claim to attention. One present-day Middle East expert admits to having long interpreted the expression as a reference to Istambul's splendid natural harbor. This individual is probably not unique and could perhaps claim to be relatively well informed. When the Sublime Porte still existed, Westerners who spent time in Istanbul knew the term as a designation for the Ottoman government, but few knew why the name was used, or what aspect of the Ottoman government it properly designated. What was the real Sublime Porte? Was it an organization? A building? No more, literally, than a door or gateway? What about it was important enough to cause the name to be remembered? In one sense, the purpose of this book is to answer these questions. Of course, it will also do much more and will, in the process, move quickly onto a plane quite different from the exoticism just invoked. For to study the bureaucratic complex properly known as the Sublime Porte, and to analyze its evolution and that of the body of men who staffed it, is to explore a problem of tremendous significance for the development of the administrative institutions of the Ottoman Empire, the Islamic lands in general, and in some senses the entire non-Westerrn world.
Keywords: Bureaucracy -- Turkey.; Turkey -- Politics and government -- 19th century.; Bureaucratie -- Turquie.; Empire ottoman -- Politique et gouvernement -- 19e siècle.; POLITICAL SCIENCE -- Public Affairs & Administration.; HISTORY -- Middle East -- Turkey & Ottoman Empire.; Bureaucracy; Politics and government; Turkey; Bureaucratie -- Empire ottoman -- 19e siècle.; Administration publique -- Réforme -- Empire ottoman -- 19e siècle.; 1800-1899